Investigating the Impact of Climate Change on Evapotranspiration Using Modeling - Waheed, Faten (AUC Knowledge Fountain, 2024)
The available water resources are at risk due to climate change and the increasing water demand. Evapotranspiration is a very important element in water cycle. Evapotranspiration is perceived as a linking mechanism between the surface of the land and the atmosphere. Therefore, investing appropriate approaches to estimate evapotranspiration and the implication of climate change on evapotranspiration and available water resources are of great importance for better water management and food security. Penman-Monteith (PM) equation is considered as one of the most widely used equation for estimating ETo. It is also one of the most complex energy balance equations requiring detailed metrological data. Yet, it is still widely recommended because of its detailed theoretical base and its accommodation of small time periods. Other simpler equations requiring limited data, namely Hargreaves-Samani (HS) and Blaney-Criddle (BC), required maximum and minimum temperatures only; however, the accuracy of these equations is limited to certain climatic regions. Therefore, developing a calibrated equation to predict ETo values similar to the obtained values by PM equation and in the same time using less weather data input will be of great importance, particularly under climate change assessment, where the future climate scenarios contain projection of maximum and minimum temperature only. The current study was conducted to assess the impact of climate change on ETo in Middel Egypt governorates using modeling approach. In this approach, a linear regression equation was established with ETo values resulted from the Penman-Monteith (PM) equation plotted as the dependent variable and ETo values from HS equation plotted as the independent variable. Similar approach was done between ETo values resulting from PM equation and ETo values from BC equation. The intercept (a) and calibration slope (b) of the best fit regression line were used as regional calibration coefficients for each governorate. Later, the data of wheat planted in a field experiment in Minia governorate was used to check the accuracy of the calibrated equations using SALTMED model to assess the sustainability of the calibrated equations. The same field experiment and simulation model were used to study the implication of climate change on evapotranspiration, which will also affect water management and food security. Two climate change scenarios were adopted: SSP1-2.6 in 2060-2079 and 2080-2099; SSP5-8.5 in 2060-2079 and 2080-2099. The results showed that there was a deviation that might happen from one season to another, which would have reduced the efficiency of the calibrated equations. Yet, using the average of ETo for 3 years showed better 3 results compared to considering one year only. Under climate change, the results of SALTMED model revealed that high temperature is expected to accelerate wheat growth and shorten crop season length, which will affect water productivity and crop production. Consequently, this will affect achieving sustainability under climate change. Yet, it must be mentioned that adopting crop rotation is of great significance in mitigating the impact of climate change on evapotranspiration as cultivating wheat after one legume crop showed better results and increased resiliency of wheat to climate change compared to cultivating wheat after maize.